Invasive Thrips (Thrips parvispinus) and Their Management in Chilies - Ramesha, N. M.; Asritha, Chava; Satwika, Maharaj; Kumar, Methuku Anil (Chronicle of Bioresource Management, 2024)
Thrips parvispinus (Karny) is an invasive pest belonging to the family Thripidae and order Thysanoptera. In chilli, yield loss can vary from 40 to 80%. It feeds between the margins of leaves, sucking the sap from young leaves, blossoms and budding fruits. Old leaves have a silvery look. Scraping the petals causes the flower to drop and the fruit to set abnormally. While the adult prefers to live in flowers, the nymph prefers to live on leaves. Community approach in pest management helps in better management of thrips particularly when the incidence is flaring up at large scale.